Principles of Reforestation of Degraded Areas and Rehabilitation Planting - Bhadran, C. A. R. (Indian Forester, 1957)
The general principles involved in the use of forestry means for improving degraded watersheds are explained. Besides restoration of vegetative cover by protective measures or by removing or restricting the causes of degrade, the importance of rehabilitation planting is emphasized. Giving due consideration to the degraded condition of the area, procedure is indicated for selection of species, of techniques of planting, of spacing, etc. - in order that maximum soil cover may result in the shortest time possible. All forestry operations in a watershed should be directed much more towards the control of rainfall and run-off to result in maximum sustained production of water and the control of soil erosion than towards the production of forest products or of financial returns.